YOUNG PEOPLE ARE INCREASING A SPIRITUAL CULTURE PLACE OF NATIONAL MENTALITY - Abdurakhimovich, Mamanov Jamoliddin (International Journal of Psychosocial Rehabilitation, 2020)
This paper makes analyses of the young people are increasing a spiritual culture place of national mentality. Therefore, analyses of the spiritual culture were conducted in the research mythology. It concluded with the vivid points of the national mentality